In key skills - García Martínez, Paula (Avances en Supervisión Educativa, 2014)
This article presents the processes and actions made in the implementation of new methodologies for the acquisition of skills in a secondary school. The articulation of elements, actions and essential procedures on the introduction of innovation in the school are presented: Background and analysis of the center in context. It present the actions for the integration of learning skills and methodologies school. They are listed the procedures for monitoring and evaluating innovation, the accountability, the internal assessment and the external evaluation. The article concludes with some reflections on educational innovation and supervision in innovative schools.